DIFFERENTIAL INTERFEROMETRY AS A TOOL OF AN EARLY WARNING SYSTEM IN REDUCING THE VOLCANO RISK: THE CASE OF NISYROS VOLCANO - Parcharidis, Is.; Lagios, E.; Sakkas, V. (Bulletin of the Geological Society of Greece, 2018)
In this study an attempt to evaluate the possibility to use the interferometric (InSAR) technique as an operational tool in an early warning system concerning the volcanic hazard, is presented. The InSAR techniques was appied in Nisyros volcanic island which during 1996-1998 show an intensive seismic unrest. Two interferometric images were created covering the period before the seismic activity (1995-1996). In the two interferometric images fringe patterns of deformation were recognized related to the ground deformation occured before the seismic unrest period. The operational capabilities of the technique is mainly restricted by the low repetitevily of the image aquisitions and the parameters to take in consideration like perpendicular baseline, atmospheric conditions etc